Using fish to understand how cities affect sexual selection before and after mating - Marques, Piatã; Zandonà, Eugenia; Amaral, Jeferson; Selhorst, Yasmin; El-Sabaawi, Rana; Mazzoni, Rosana; Castro, Letícia; Pilastro, Andrea (Frontiers in Ecology and Evolution, 2022)
Urbanization transforms natural and agricultural areas into built landscapes. Such profound habitat alteration imposes strong pressure for phenotypic trait changes through processes related to natural and/or sexual selection. Evidence for how natural selection drives changes to traits in urban biota is increasing, but little is known about the role of sexual selection. In this study, we assess the effect of urbanization on the expression and interaction of males` pre-mating traits (body size and color) and a post-mating trait (sperm load). We used a widespread invasive species, the guppy (Poecilia reticulata), which is a well-known model for studying sexual selection, but has never been studied in urban systems for this purpose. We found that urbanization did not affect mean body size or condition, but it resulted in size-dependent reductions in the expression of orange and iridescent colors, as well as sperm load. Orange color was reduced in small urban guppies, while the iridescent colors were reduced in large urban guppies compared to non-urban guppies. Difference in sperm load was only found in large males, with lower sperm load in urban guppies. The relationship between orange color and sperm load was positive in urban guppies but negative in non-urban guppies, while the association between iridescent color and sperm load followed the opposite pattern. Our findings suggest that sexual selection on pre- and post-mating traits is weaker in urban than non-urban systems and that interactions between such traits are context dependent. These responses can be related to the pollution and altered visual environment of urban systems and provide an opportunity to advance our understanding of the mechanisms determining adaptation in cities.